PENINGKATAN PEMBELAJARAN KETERAMPILAN BERBICARA DENGAN MENERAPKAN MODEL PAIKEM BAGI SISWA KELAS IV SDN 24 KOTO BERAPAK KECAMATAN BAYANG - ZENDRA WATI (Inovasi Pendidikan, 2017)
Learning skills speak one of them can be applied to the model PAIKEM. PAIKEM Model provides an opportunity for students to develop their ability to speak. Siswalah become a major center in the learning process while the teacher only as a motivator who always give encouragement and motivation to students. Implementation of learning conversational skills by applying the model PAIKEM, can develop their speaking skills well. This is evidenced by improvements in the ability of students in activities unrequited rhyme with due regard to the choice of words, pronunciation, intonation, stress and precise expression. As well as the execution of activities megomentari unrequited rhyme with attention to word choice and polite language. Rate speaking skills by applying the model PAIKEM, proven to provide motivation for students to improve their speaking skills, especially in the use of word choice, pronunciation, intonation, stress, and precise expressionKeywords: speaking skills, model PAIKEM, students